Etoricoxib-induced pretibial erythema and edema - Pramod Kumar (Wolters Kluwer Medknow Publications, 2015)
Cyclooxygenase inhibitors were developed in the quest of enhanced analgesic efficacy devoid of gastric side effects. Etoricoxib is a second-generation cox-2 inhibitor and as its use increases so do the reports of side effects. We report a case of extoricoxib-induced pretibial erythema and edema; and review the literature.